The Metastatic Capacity of Melanoma Reveals Alternative Pathways of Cancer Dissemination - Michela Corsini; Cosetta Ravelli; Elisabetta Grillo; Stefania Mitola (International Journal of Translational Medicine, 2021)
For many years the growth of solid tumors has been associated with their vascularization. The new vessels are needed to deliver oxygen and nutrients within the tumor mass. At the same time, these poorly stabilized vessels act as “Trojan horses” and open a way out for cancer cells. More recently, tumors have been identified whose growth appears to be independent of endothelial cell activity. Here we describe the ability of cancer cells to differentiate and reorganize themself in channels similar to blood vessels containing blood flow, overcoming the need for the angiogenic process of tumor vascularization. Together with the new vessels arising both from angiogenic and vasculogenic processes, these vessel-like structures can be exploited by tumor cells as a guide for migration and metastatic dissemination. In addition to classical intravascular dissemination, cancer cells can acquire pericytic features, interact with the endothelial basal lamina and migrate toward vessels or outside of the vessels. As expected, these alternative tumor behaviors assume greater importance if we consider that drugs with anti-angiogenic action directed against endothelial cells or their ligands are currently used in cancer therapy.